2007
DOI: 10.1159/000103886
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Serological Panel Test in the Assessment of Gastritis in Symptomatic Children

Abstract: Background: Non-invasive methods are advisable for the detection of Helicobacter pylori-related chronic gastritis in pediatric patients. Serum pepsinogens I and II (sPGII and sPGII), gastrin-17 (G-17) and anti-H. pylori antibodies (IgG-Hp) have been proposed as a ‘serological gastric biopsy’. Aim: To assess H. pylori infection and to evaluate gastric mucosa status in a pediatric population by means of serological parameters such as sPGI, sPGII, G-17 and IgG-Hp. Methods: 45 consecutively children evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
29
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 86 publications
12
29
1
Order By: Relevance
“…[1,16] The performance of both serum and saliva immunoassays were concordant with the detection of HP in biopsies from patients with DU and approaches the fi ndings in patients with gastritis. These results are similar to previous reports, which also documented the good sensitivity and specifi city of these assays, [6,17] but a recent report from Canada demonstrated a low sensitivity and specifi city of the saliva ELISA test. [18] However, these differences can be attributed to several factors such as the type of population studied, decreased saliva fl ow due to pre-endoscopy anxiety, or differences of HP strains.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[1,16] The performance of both serum and saliva immunoassays were concordant with the detection of HP in biopsies from patients with DU and approaches the fi ndings in patients with gastritis. These results are similar to previous reports, which also documented the good sensitivity and specifi city of these assays, [6,17] but a recent report from Canada demonstrated a low sensitivity and specifi city of the saliva ELISA test. [18] However, these differences can be attributed to several factors such as the type of population studied, decreased saliva fl ow due to pre-endoscopy anxiety, or differences of HP strains.…”
Section: Discussionsupporting
confidence: 91%
“…[2,3] For quick offi ce evaluation of dyspepsia and population-based studies, a simple, rapid, reliable and an inexpensive test is highly desirable. [4] Because of their reported high sensitivity and specifi city, [5,6] commercially available antibody tests seem to be well suited for epidemiological surveys, practically among children and untreated patients. [7][8][9][10] Since the pattern of HP infection in the developing world is quite distinct from that in the Western countries [11] and because the economic constraints make invasive tests diffi cult to perform, the search for reliable and cheap tests that suit such situations becomes necessary.…”
Section: Introductionmentioning
confidence: 99%
“…investigated serum levels of these factors in children with H. pylori infection and identified significantly elevated PGII and decreased I/II ratios. The significant elevation of PGI was confirmed in children aged >10 years old 33 . In the present study, although we observed few atrophic changes in chronically H. pylori ‐infected mucosa, most patients developed nodular gastritis as children.…”
Section: Discussionsupporting
confidence: 70%
“…In most cases, infected children are asymptomatic, but some patients develop gastritis and peptic ulcer diseases [12], [13]. Moreover, some non-gastric diseases, such as iron-deficiency anemia and epilepsy, have been suggested to be associated with H. pylori infection [14][16].…”
Section: Introductionmentioning
confidence: 99%